Breaking bad news: tackling cultural dilemmas. Issue 2 (24th March 2021) - Holmes, Sophie Nilusha; Illing, Jan
Abstract: Requesting that serious diagnoses be concealed from patients, a widespread phenomenon in many cultures, presents a professional dilemma. Practical and sensitive communication strategies are needed. Methodology: In this paper, we use analysis of the existing literature to develop a communication tool for practitioners facing requests for diagnostic non-disclosure. Our approach builds on existing strategies, in providing a mnemonic communication tool, permitting more than one outcome, and focusing on the need for mutual understanding and cooperation. Results: Existing work on this dilemma highlights the need to appreciate the family's standpoint, affirm their benevolent intentions and correct misperceptions. To this end, we have developed a mnemonic tool, 'ARCHES', to be used in situations where the family has requested diagnostic non-disclosure. The model has six stages: acknowledge the request for non-disclosure, build the relationship, find common ground, honour the patient's preferences and outline the harm of non-disclosure, provide emotional support and devise a supportive solution. Conclusion: Facing requests for diagnostic non-disclosure is a challenge of communication. The dilemma is particularly marked when practising across cultures. Our model gives a structure for building rapport with the family and realigning their misperceptions while upholding the patient's right to knowledge.